2000
DOI: 10.1557/proc-643-k8.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Tribological and Oxidative Properties of AlPdMn Quasicrystals and Their Cubic Approximants

Abstract: An experimental comparison has been made between the properties of the surfaces of an Al 70 Pd 21 Mn 9 quasicrystal and its Al 48 Pd 42 Mn 10 approximant. The Al 70 Pd 21 Mn 9 sample was a single grain icosahedral quasicrystal cut to expose its five-fold symmetric (000001) surface. The approximant was polycrystalline β-phase Al 48 Pd 42 Mn 10 , which has a CsCl-type cubic structure. Surfaces of both were prepared under ultra-high vacuum (UHV) conditions and then used for comparative measurements of their frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Until now, most experimental studies of tribology on quasicrystals [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been carried out under conditions in which irreversible ͑plastic͒ deformation takes place during sliding. Frictional energy dissipation measured under such conditions includes contributions from such diverse factors as the breaking of chemical bonds, generation of point defects, interactions with wear debris, phase transformations near the sliding track, and in crystalline materials by creation of dislocations and propagation of slip planes in specific crystallographic directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, most experimental studies of tribology on quasicrystals [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been carried out under conditions in which irreversible ͑plastic͒ deformation takes place during sliding. Frictional energy dissipation measured under such conditions includes contributions from such diverse factors as the breaking of chemical bonds, generation of point defects, interactions with wear debris, phase transformations near the sliding track, and in crystalline materials by creation of dislocations and propagation of slip planes in specific crystallographic directions.…”
Section: Introductionmentioning
confidence: 99%
“…A set of studies in ultrahigh vacuum has been reported by Gellman et al, 8,10,11 who found that the friction coefficient of clean, single-grain quasicrystalline Al-Pd-Mn is half that of a crystalline Al-Pd-Mn alloy with similar stoichiometry. However, they found no variation in friction coefficient across a series of quasicrystalline-related phases in the Al-Cu-Fe family, leading them to suggest that friction is not related to atomic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The very first steps of the oxidation of quasicrystals based on aluminum [4][5][6][7][8][9][10][11][12][13] and the effect of oxygen on thin films formation [14,15] have been the subject of many studies. In particular, for i-AlCuFe, two temperature regimes were pointed out for the oxidation mechanism of the surface by pure oxygen, each preceded by a chemisorption step.…”
Section: Introductionmentioning
confidence: 99%
“…AES shows that exposure to O 2 results in the formation of a thin film of aluminum oxide that passivates the surface against further oxidation. This is similar to the oxidation of the surface of aluminum itself [ 101,102]. These films have an influence on the frictional properties of the surface.…”
Section: Tribology Of Quasicrystalsmentioning
confidence: 74%